Spatial and temporal distribution of butterfly in highland and lowland forests of Johor - Ismail, Norradihah (2017)
Johor is a fast developing state and if unchecked could lead to loss of biodiversity. Among insects, butterfly is an important bioindicator of environmental changes. For effective management purposes, a baseline data of butterfly is needed. Samplings were carried out in various forest types: Taman Negara Johor Endau Rompin (TNJER), a lowland forest (30 to 100 m above sea level (a.s.l.)) and Taman Negara Johor Gunung Ledang (TNJGL), a highland forest (400, 800 and 1200 m a.s.l.). The objectives of this research were (i) to document butterfly diversity in TNJER and TNJGL, (ii) to analyse species diversity patterns based on faunistic aspect, (iii) to determine temporal distributions based on seasonal variations and (iv) to relate the effects of environmental parameter on butterfly’s diversity. Samplings were done manually (along 2 km transect) and trapping using fruit bait (rotten banana and pineapple) over a period of 15 months from April 2014 until July 2015. A total of 1125 individuals comprising 191 butterfly species from five families were collected and recorded. Nymphalidae was the most well- represented family. The values of Shannon Diversity Index (H’) and Species Evenness Index (E’) were higher in TNJER (H’=4.123; E’=0.471) than TNJGL (H’=3.405; E’=0.235). Based on elevations, 400 m a.s.l. had the highest species index (H’=4.169) and more even distribution (E’=0.660) compared to the two higher altitudes. Temporally, the diversity index was the highest in May (H’=3.357) and lowest in June (1.639) at TNJER and indicated the highest species similarity occurring between April and May. In TNJGL, the diversity was the highest in May (H’=3.626) and lowest during June (2.012) and resulted greatest similarity between June and August. However, this study found no significant relationships (p> 0.05) between environmental parameters (humidity and temperature) and diversity (species richness and abundance) at different elevations. The spatial and temporal approaches used in this study would increase in understanding on the impact of altitudinal and climatic changes on butterfly’s diversity and provide baseline data for Johor that would be useful for biodiversity monitoring and conservation of the protected areas.